2019
DOI: 10.1111/jfd.12972
|View full text |Cite
|
Sign up to set email alerts
|

The role of rpoS in the regulation of Vibrio alginolyticus virulence and the response to diverse stresses

Abstract: Vibrio alginolyticus is a leading aquatic pathogen, causing huge losses to aquaculture. rpoS has been proven to play a variety of important roles in stress response and virulence in several bacteria. In our previous study, upon treatment with Cu2+, Pb2+, Hg2+ and low pH, the expression levels of rpoS were downregulated as assessed by RNA‐seq, while impaired adhesion ability was observed, indicating that rpoS might play roles in the regulation of adhesion. In the present study, the RNAi technology was used to k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 59 publications
3
9
0
Order By: Relevance
“…Biofilm is a sophisticated bacterial community and it increases resistance in bacteria to disinfectant agents. The present study revealed that RpoS promoted the biofilm formation by S. baltica X7 at 30°C, and the same phenomenon was also reported in some other bacterial species such as Y. Pseudotuberculosis, P. aeruginosa and Vibrio alginolyticus, where rpoS was shown to involve in regulation of the synthesis of exopolysaccharides or flagellar genes, and similarly promoted the biofilm formation (Guan et al 2015;Bouillet et al 2019;Huang et al 2019).…”
Section: Regulation Of Biofilm Formation By Rpossupporting
confidence: 88%
See 1 more Smart Citation
“…Biofilm is a sophisticated bacterial community and it increases resistance in bacteria to disinfectant agents. The present study revealed that RpoS promoted the biofilm formation by S. baltica X7 at 30°C, and the same phenomenon was also reported in some other bacterial species such as Y. Pseudotuberculosis, P. aeruginosa and Vibrio alginolyticus, where rpoS was shown to involve in regulation of the synthesis of exopolysaccharides or flagellar genes, and similarly promoted the biofilm formation (Guan et al 2015;Bouillet et al 2019;Huang et al 2019).…”
Section: Regulation Of Biofilm Formation By Rpossupporting
confidence: 88%
“…Moreover rpoS also up-regulated the expression of chemotaxis proteins related to motility in V. cholerae, V. alginolyticus(Ringgaard et al 2015;Huang et al 2019). It indicated that RpoS-mediated swimming motility in bacteria is complex…”
mentioning
confidence: 92%
“…Each year, the fish diseases caused by this pathogen leads to an economic loss of approximately $150 million. Recently, several proteins such as HopPmaJ [17], Acfa [18] and VscO [19] have been reported to be involved in invasion of the host as a virulence effector, as well as protein RpoS affect on adhesion to bacteria, growth, hemolysis, biofilm production, movement [20], and SodB protein influence of bacterial motility and adhesion, leading to changes in bacterial virulence [21]. However, the intrinsic virulence mechanisms are still largely unknown, especially for the role of Kace modification.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several Vibrio species are to a certain extent pathogenic, and thus constitute important microbial risk agents in water threatening environmental and human health. For example, V. parahaemolyticus , V. cholerae , V. vulnificus , V. harveyi and V. fluvialis are pathogens that cause gastroenteritis, sepsis and necrosis in animals and humans [14] , [19] , [36] , [54] . Hence, in-depth knowledge on biogeographic patterns of Vibrio species helps to predict the response of coastal water ecosystems to changing environmental factors.…”
Section: Introductionmentioning
confidence: 99%